ChemInform Abstract: Theoretical Investigations of Novel Zinc Oxide Polytypes and In‐Depth Study of Their Electronic Properties. Issue 25 (5th June 2015) - Zagorac, D.; Schoen, J. C.; Zagorac, J.; Jansen, M.
Abstract: Possible stable polytypes of ZnO are predicted using simulated annealing and threshold runs with an empirical potential followed by local minimization on ab initio level.